Does financial technology matter? Evidence from an alternative banking system - Dur Almulla; Abdullah A. Aljughaiman (Cogent Economics & Finance, 2021)
The purpose of this study is to examine the impact of the financial technology (fintech) services provided by banks on their performance. We also investigate the influence of fintech firms' growth (as competitor firms) on banks' financial performance. We extend our analysis to investigate the differences between conventional banks (CBs) and Islamic banks (IBs) in this relationship and utilise a sample of 40 listed banks from Gulf Cooperation Countries, where fintech growth was impressive in the period 2014-2019. We find a negative relationship between fintech services and bank performance for both types of bank. Furthermore, we show that the growth of fintech firms in a country negatively influences CBs' financial performance but has no significant impact on IBs' performance. In addition, we test our hypotheses through multiple additional tests and robustness tests, such as the generalised method of moments. The findings could be relevant to banks, policy makers, and academic research.
Keywords: G20; G21; 330; conventional banks; financial performance; fintech firms; Fintech services; Islamic banks